Braak's Unfinished Hypothesis: A Clinicopathological Case Report of α‐Synuclein Peripheral Neuropathy Preceding Parkinsonism by 20 Years. Issue 7 (13th August 2021) - Donlon, Eoghan; Lynch, Rionagh; Murphy, Olwen C.; Farrell, Michael; Noel, Jaques; Keogan, Mary; O'Connell, Martin; Lynch, Timothy
ABSTRACT: Background: α‐synuclein aggregates in the form of Lewy bodies and Lewy neurites are the pathological hallmark of Parkinson disease (PD) and dementia with Lewy bodies (DLB). Autopsy studies suggest that α‐synuclein aggregates appear in localized areas of the central nervous system before spreading in a sequential pattern from the brainstem to the cerebral cortex, known as the Braak hypothesis. Increased prevalence of peripheral neuropathy in PD is recognized, with multiple hypothesized mechanisms including α‐synuclein deposition. Method: We describe a patient who developed a peripheral sensory neuropathy at age 60, which progressed insidiously over the following decade. Results: During the patient's eighth decade, the patient developed a fluctuant cognitive disturbance with hallucinations before becoming overtly parkinsonian at age 78 years leading to a diagnosis of DLB. At this point, histology slides from a sural nerve biopsy taken at age 72 were re‐evaluated and immunohistochemistry demonstrated α‐synuclein deposition. Conclusion: This case provides important in vivo clinical correlation for the Braak hypothesis, extending its scope beyond idiopathic PD. A growing body of evidence supports the α‐synuclein spreading hypothesis that posits the pathologic process begins in the peripheral nerves and spreads trans‐synaptically to the CNS in an ascending pattern.